2003
DOI: 10.1021/tx025636d
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Coumarins Inhibit Human Cytochromes P450 and Block Benzo[a]pyrene and 7,12-Dimethylbenz[a]anthracene DNA Adduct Formation in MCF-7 Cells

Abstract: Naturally occurring coumarins (NOCs) inhibit polycyclic aromatic hydrocarbon-induced skin tumor initiation in mice by blocking cytochrome P450 (P450)-mediated bioactivation of benzo[a]pyrene (B[a]P) and 7,12-dimethylbenz[a]anthracene (DMBA). Bergamottin selectively inhibits tumor initiation by B[a]P, whereas imperatorin and isopimpinellin inhibit tumor initiation with both carcinogens. The goals of the current study were to examine the ability of NOCs to inhibit human P450s in vitro and to establish whether NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 33 publications
(60 reference statements)
1
39
0
Order By: Relevance
“…When applied topically to mouse epidermis BG decreased covalent binding to DNA of benzo [a]pyrene (B [a]P). The effect was dosedependent (a 72% decrease at a concentration of 400 nM) [105,109] and remarkably selective, as it did not occur with 7,12-dimethylbenz [a]anthracene (DMBA). This selectivity might be explained by the finding that BG preferentially inhibited P450 1A1, the enzyme that converts B [a]P to the corresponding 7,8 dihydrodiol, rather than other isoform of CYP that act on DMBA [108].…”
Section: Geranyloxyfurocoumarinsmentioning
confidence: 99%
See 2 more Smart Citations
“…When applied topically to mouse epidermis BG decreased covalent binding to DNA of benzo [a]pyrene (B [a]P). The effect was dosedependent (a 72% decrease at a concentration of 400 nM) [105,109] and remarkably selective, as it did not occur with 7,12-dimethylbenz [a]anthracene (DMBA). This selectivity might be explained by the finding that BG preferentially inhibited P450 1A1, the enzyme that converts B [a]P to the corresponding 7,8 dihydrodiol, rather than other isoform of CYP that act on DMBA [108].…”
Section: Geranyloxyfurocoumarinsmentioning
confidence: 99%
“…BG also prevented B [a]P bioactivation by CYP. At a concentration of 800 nM, BG inhibited skin tumor initiation in vivo [105,109]. Taking into account the effects on CYP exerted by BG, isoimperatorin and isopimpinellin, Di Giovanni and coworkers sketched the following mechanism of cancer prevention by these furanocoumarins (Scheme 4).…”
Section: Geranyloxyfurocoumarinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bergamottin, a natural furanocoumarin abundantly present in grapefruit juice, has been demonstrated to exhibit anticancer effects in a variety of human cancers, including chronic myelogenous leukemia (11), multiple myeloma (12), skin cancer (13) and breast cancer (14). It has been reported that bergamottin enhances tumor necrosis factor-induced apoptosis in human chronic myelogenous leukemia via inactivation of nuclear factor-κB signaling (11).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Therefore, selective inhibition of P450 1A2 is a potential molecular target for chemoprevention of environmental arylamine-caused DNA mutations and carcino-genesis. 3 Certain compounds with varying molecular structures have been shown to effectively inhibit P450 1A2, including aryl hydrocarbons, stilbenoids, flavonoids, coumarins, and anthra-quinone, etc. 410 However, because of the high degree of similarity between P450 1A2 and P450s 1A1 and 1B1 (sharing 80% and 40% amino acid sequence identity, respectively), most P450 1A2 inhibitors also show some extent of inhibitory activity toward P450s 1A1 and 1B1.…”
Section: Introductionmentioning
confidence: 99%